Conductive paste, electronic component, and laminated ceramic capacitor
By using a mixed system of cellulose and polyvinyl acetal in the conductive paste and forming polymer compounds through sulfur atom bonding, the problem of incompatibility of the binder resin combination in the conductive paste is solved, the excellent dispersion of the conductive powder and the high smoothness of the dry film are achieved, and the high capacity requirement of the laminated ceramic capacitor is met.
Patent Information
- Application Number
- CN202380052573.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the combination of the two organic binder resins in the conductive paste is usually incompatible, resulting in a significant reduction in function, and the smoothness and dispersion of the dry film are insufficient, making it difficult to meet the high capacity requirements of the laminated ceramic capacitor.
By introducing a mixed system of cellulose and polyvinyl acetals into the conductive paste, and forming polymer compounds through sulfur atom bonding, the molar ratio of sulfur atoms is controlled to be between 0.3 and 1.7 to improve the compatibility and dispersion of the binder resin.
Excellent dispersion of the conductive powder in the conductive paste and high surface smoothness of the dry film are achieved, and the clinging of the internal electrode layer and the film-film quality of the electrode pattern of the laminated ceramic capacitor are improved.
Smart Images

Figure CN119547158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste, an electronic component, and a multilayer ceramic capacitor. Background Art
[0002] As electronic devices such as mobile phones and digital devices become smaller and more powerful, electronic components including multilayer ceramic capacitors are also expected to be smaller and have higher capacitance. Multilayer ceramic capacitors have a structure in which multiple dielectric layers and multiple internal electrode layers are alternately stacked. By thinning these dielectric layers and internal electrode layers, miniaturization and higher capacitance can be achieved.
[0003] Multilayer ceramic capacitors are manufactured, for example, as follows. First, a conductive paste for internal electrodes is printed (applied) in a predetermined electrode pattern on the surface of a raw sheet containing a dielectric powder such as barium titanate (BaTiO3) and a binder resin such as a polybutyral resin, and dried to form a dry film. Next, a laminate is formed in which the dry film and the raw sheet are stacked in an alternating overlapping manner, heated and pressed to form an integrated state. The laminate is cut, and after being subjected to an organic binder removal treatment in an oxidizing atmosphere or an inactive atmosphere, it is fired to obtain a fired chip. Next, a slurry for external electrodes is applied to both ends of the fired chip, and after firing, the surface of the external electrode is plated with nickel, etc., to obtain a multilayer ceramic capacitor (MLCC).
[0004] In recent years, MLCC has been required to be further miniaturized and increased in capacity. For example, for internal electrodes using nickel, etc., research has been conducted on the thinning of dense and continuous electrode films. For ceramic dielectric materials and dielectric layers using them, research has been conducted on high dielectric constants and thin layers. Materials with dielectric layer thicknesses of 1.0 μm or less have also been put into practical use. Moreover, it is also expected that the electrode film will be less than 1.0 μm.
[0005] The required characteristics for miniaturization and high capacity of MLCC can be listed as suppressing the reduction of insulation resistance under high temperature and high voltage, that is, high reliability. It is said that the main reason for the reduction in insulation resistance is that the surface of the Ni electrode layer sandwiching the dielectric layer is uneven after the firing process, and the electric field is concentrated on the convex part. In the firing process, the Ni electrode layer is formed through the process of sintering and densification of Ni powder. However, the fine Ni powder sintered quickly, so the electrode was easily interrupted and spheroidized. As a result, the effective electrode area of the Ni electrode layer was reduced, the capacity was reduced, and the unevenness on the surface of the Ni electrode layer led to a reduction in insulation resistance.
[0006] If the MLCC is thinned, the adhesion between the green sheet and the internal electrode layer will decrease, and problems such as curling and stacking deviation will occur frequently due to insufficient adhesion during stacking. Therefore, internal electrode slurry with plasticizers added is used. However, due to the plasticizer, the elastic modulus of the printed film decreases significantly, and it is easy to soften and deform. Therefore, even if the adhesion with the green sheet is improved, the disadvantages such as poor cutting of the internal electrode layer will become greater. In addition, due to the plasticizer, the amount of gas generated in the organic binder removal process increases, which becomes the cause of cracks.
[0007] When ceramic green sheets are stacked and pressed in the thickness direction, if the adhesion between the green sheets is weak, the bonding between the green sheets is poor. This poor bonding, for example, causes short circuits in multilayer ceramic capacitors. In particular, due to the multilayer requirements of MLCC, it is necessary to use fine-grained dielectric powder to reduce the thickness of each dielectric layer. In addition, it is necessary to increase the number of stacking layers, so it is expected to improve the poor bonding. If the bonding between the green sheets is weak, structural defects such as delamination, voids, and cracks will occur during firing, reducing the yield of MLCC.
[0008] In order to improve such poor adhesion, the following measures 1) and 2) are conceivable.
[0009] 1) It is possible to increase the amount of binder or thickener in the conductive paste, but simply increasing their amounts does not improve the adhesion. On the contrary, when increasing their amounts, the amount of organic substances such as organic binder and thickener added to the conductive paste increases, and these organic substances become the cause of difficulty in removing the organic binder. Even if the organic binder is removed, the remaining organic substances (carbon residue) may sometimes cause structural defects in the subsequent firing process.
[0010] 2) When stacking a plurality of ceramic green sheets having conductive paste films formed thereon, the surface of the coating film made of the conductive paste is smoothed, thereby increasing the contact area between the conductive paste film and the ceramic green sheets, and as a result, improving adhesion.
[0011] Although the purpose of improving the close contact between the internal electrode and the raw sheet is to prevent cracking, if butyral resin is used as the resin, it is possible to prevent the electrode from peeling off during cutting. So far, organic binders mainly use cellulose resins such as ethyl cellulose, but cellulose resins have high compatibility with various solvents and are effective in giving the conductive paste the rheological properties as the purpose, but on the other hand, they themselves are not very thermoplastic, so they have the disadvantage that the dry body part of the conductive paste and the raw sheet on the upper surface have almost no close contact during hot pressing. As a result, there has been no conductive paste for the internal electrodes of the raw sheet screen-printed with conductive paste, which can further improve the hot pressing properties of the raw sheet on the upper surface, prevent the stacking deviation of the electrodes inside the chip, improve the electrode alignment, and prevent the chip from cracking and peeling, and can cope with high-layer stacking.
[0012] Therefore, the internal electrode paste may contain an organic resin, and the organic binder resin is preferably a mixed system of ethyl cellulose (EC) and polyvinyl butyral (PVB).
[0013] Ethyl cellulose (EC) has good solubility in solvents, printability, combustion decomposition, etc., and can be used as a binder for internal electrode slurry. In addition, by using polyvinyl butyral (PVB) for green sheets as an organic binder resin, the adhesion strength between the green sheets and the dried film of the internal electrode slurry can be improved.
[0014] Patent Documents 1 and 2 disclose conductive pastes containing a cellulose resin and a polyvinyl butyral resin as a binder resin, and disclose that the adhesiveness with ceramic green sheets is improved.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent No. 5299904
[0018] Patent Document 2: Japanese Patent No. 5224722 Summary of the invention
[0019] Problems to be solved by the invention
[0020] However, generally speaking, when two different organic binder resins are mixed, they become an almost incompatible (non-compatible) combination. In the case of an incompatible combination of two organic binder resins, the two organic binder resins are basically not fused but exist independently, so not only can the expected performance not be exerted, but the functions are mostly significantly reduced.
[0021] In addition, if the resin is difficult to dissolve in the solvent, the smoothness of the slurry dried film deteriorates. For example, when EC and PVB are mixed, a typical "sea island structure" is observed, and phase separation is confirmed. As a result, the distribution of inorganic particles (conductive particles, ceramic powder) in the dry film is made uneven. In this way, the combination of organic materials in the slurry composition affects the dispersibility of inorganic particles (conductive particles, ceramic powder) in the dry film.
[0022] By making polymers that are originally immiscible compatible with each other, it is possible to combine the advantages of both, stabilize the interface between different polymers, and realize a uniform and stable dispersion structure.
[0023] In addition, in the conductive paste disclosed in Patent Documents 1 and 2, since polyvinyl butyral resin is included, the adhesion between the dry film and the green sheet can be improved. However, in these technologies, since cellulose resin and polyvinyl butyral resin are used together, due to the poor compatibility of the two resins, sometimes the dispersion of conductive powder and ceramic powder in the conductive paste is insufficient, or the density and smoothness of the dry film of the conductive paste become insufficient. Such dry film characteristics cannot be said to be sufficient to cope with the high capacity of multilayer ceramic capacitors in recent years.
[0024] In view of such circumstances, an object of the present invention is to provide a conductive paste, an electronic component, and a multilayer ceramic capacitor that can form an internal electrode layer having a smooth dry film and excellent adhesion in a conductive paste using micronized conductive powder and ceramic powder for miniaturization and thinning of multilayer ceramic electronic components.
[0025] Means used to solve problems
[0026] In order to solve the above-mentioned problems, the conductive paste of the present invention comprises a conductive powder, a ceramic powder, a dispersant, a binder resin and an organic solvent, wherein the binder resin comprises cellulose, polyvinyl acetal, and a polymer compound in which a cellulose-based compound and a polyvinyl acetal-based compound are bonded via sulfur atoms, and the molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.3 to 1.7.
[0027] It is also possible that the cellulose-based compound is a cellulose derivative having a thiol group or a vinyl group, and the polyvinyl acetal-based compound is a polyvinyl acetal resin having a thiol group or a vinyl group. When the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group that reacts with the thiol group, and when the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group that reacts with the vinyl group.
[0028] The cellulose derivative may be ethyl cellulose having a thiol group or a vinyl group, and the polyvinyl acetal resin may be polyvinyl butyral having a thiol group or a vinyl group.
[0029] It may also be that the cellulose-based compound is a first esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose, and the polyvinyl acetal-based compound is a second esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of polyvinyl acetal, when the first esterification product has a thiol group, the second esterification product has a vinyl group, and when the first esterification product has a vinyl group, the second esterification product has a thiol group, and the polymer compound is a thiol-ene reaction product of the first esterification product and the second esterification product.
[0030] Alternatively, the first esterification product may be a product formed by dehydration condensation of a carboxyl group of 3-allyloxypropionic acid and a hydroxyl group of ethyl cellulose, and the second esterification product may be a product formed by dehydration condensation of a carboxyl group of 3-mercaptopropionic acid and a hydroxyl group of polyvinyl butyral.
[0031] Alternatively, the conductive powder may be nickel powder.
[0032] The number average particle size of the conductive powder may be 0.05 μm or more and 1.0 μm or less.
[0033] Alternatively, the ceramic powder may contain barium titanate.
[0034] The ceramic powder may have a number average particle size of 0.01 μm or more and 0.5 μm or less.
[0035] The content of the ceramic powder may be 1 mass % or more and 20 mass % or less.
[0036] The conductive paste of the present invention can be used for internal electrodes of multilayer ceramic components.
[0037] In order to solve the above-mentioned problems, the electronic component of the present invention is an electronic component formed using the conductive paste of the present invention.
[0038] In order to solve the above-mentioned problems, a multilayer ceramic capacitor of the present invention includes a laminated body including at least dielectric layers and internal electrode layers, wherein the internal electrode layers are formed using the conductive paste of the present invention.
[0039] Effects of the Invention
[0040] The conductive paste of the present invention has excellent dispersibility of conductive powder and has high surface smoothness in the dried film after coating. In addition, the electrode pattern of electronic components such as multilayer ceramic capacitors formed using the conductive paste of the present invention also has excellent adhesion when forming thin-film electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 1 and 2 are a perspective view and a cross-sectional view showing a multilayer ceramic capacitor according to the present embodiment.
[0042] Figure 2 This is a diagram for evaluating the adhesion between a dry film obtained by printing and drying a conductive paste and a green sheet. DETAILED DESCRIPTION
[0043] Hereinafter, one embodiment of the conductive paste, electronic component, and multilayer ceramic capacitor of the present invention will be described.
[0044] [Conductive paste]
[0045] The conductive paste of the present embodiment includes conductive powder, ceramic powder, a dispersant, a binder resin, and an organic solvent. Hereinafter, each component will be described in detail.
[0046] (Conductive powder)
[0047] The conductive powder is not particularly limited, and metal powder can be used, for example, powders of one or more selected from Ni, Pd, Pt, Au, Ag, Cu and their alloys can be used. Among them, from the viewpoints of conductivity, corrosion resistance and cost, powders of Ni or its alloys are preferred. As a Ni alloy, for example, an alloy (Ni alloy) of Ni and at least one element selected from the group consisting of Mn, Cr, Co, Al, Fe, Cu, Zn, Ag, Au, Pt and Pd can be used. The content of Ni in the Ni alloy is, for example, 50% by mass or more, preferably 80% by mass or more. In addition, in order to suppress the rapid gas generation caused by partial thermal decomposition of the binder resin during the debonding process, the Ni powder can contain about hundreds of ppm of S.
[0048] The method for producing the conductive powder is not particularly limited, and examples thereof include a method of directly precipitating chloride vapor from a gas phase in hydrogen, an atomization method from molten metal, a spray pyrolysis method using an aqueous solution, a wet method of reducing a raw material metal salt in an aqueous solution, and the like.
[0049] The number average particle size of the conductive powder is not particularly limited, and can be selected according to the size of the electronic component of the object of use. The number average particle size of the conductive powder is preferably 0.5 μm or less, and more preferably 0.3 μm or less, for example, for use in multilayer ceramic capacitors that are developing thin films. When the average particle size exceeds 0.5 μm, the surface of the internal electrode becomes convex and concave, which sometimes deteriorates the electrical properties of the capacitor, so it is not preferred. In addition, the lower limit of the average particle size of the conductive powder is not particularly limited, for example, it is 0.03 μm or more. When the number average particle size is less than 0.03 μm, handling becomes extremely difficult.
[0050] The number average particle size of the conductive powder is a value obtained by observation using a scanning electron microscope (SEM), and is an average value obtained by measuring the particle sizes of a plurality of particles one by one from an image obtained by observation using the SEM at a magnification of 10,000 times.
[0051] The content of the conductive powder is preferably 30% by mass or more and less than 70% by mass, more preferably 40% by mass or more and 60% by mass or less, relative to the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0052] (Ceramic powder)
[0053] The ceramic powder is not particularly limited. For example, in the case of a conductive paste for internal electrodes of a multilayer ceramic capacitor, a known ceramic powder is appropriately selected according to the type of multilayer ceramic capacitor to be applied. The ceramic powder may be, for example, a perovskite oxide containing Ba and Ti, preferably barium titanate (BaTiO3).
[0054] As the ceramic powder, a ceramic powder containing barium titanate as a main component and oxides as a secondary component may also be used. As oxides, oxides of Mn, Cr, Si, Ca, Ba, Mg, V, W, Ta, Nb and one or more rare earth elements may be cited. In addition, as the ceramic powder, for example, a ceramic powder of a perovskite-type oxide ferroelectric in which the Ba atoms and Ti atoms of barium titanate (BaTiO3) are replaced by other atoms such as Sn, Pb, Zr, etc. may also be used.
[0055] In the conductive paste for the internal electrode, a powder having the same composition as the dielectric ceramic powder constituting the green sheet of the multilayer ceramic capacitor can also be used as the ceramic powder. This can suppress the generation of cracks caused by the mismatch of shrinkage at the interface between the dielectric layer and the internal electrode layer during the sintering process. As such ceramic powder, in addition to the above, for example, oxides such as ZnO, ferrite, PZT, BaO, Al2O3, Bi2O3, R (rare earth element) 2O3, TiO2, and Nd2O3 can be listed. In addition, one ceramic powder can be used, or two or more ceramic powders can be used.
[0056] The number average particle size of the ceramic powder is, for example, in the range of 0.01 μm to 0.5 μm, preferably in the range of 0.01 μm to 0.3 μm. By making the number average particle size of the ceramic powder in the above range, when used as an internal electrode slurry, a sufficiently fine and thin uniform internal electrode can be formed. The number average particle size is a value obtained by observation using a scanning electron microscope (SEM), and is an average value obtained by measuring the particle sizes of multiple particles one by one from an image obtained by observation using an SEM at a magnification of 50,000 times.
[0057] The content of the ceramic powder is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 3 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the conductive powder. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0058] The content of the ceramic powder is preferably 1% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 20% by mass or less, relative to the total amount of the conductive paste. When the content of the conductive powder is within the above range, the conductivity and dispersibility are excellent.
[0059] (Binder resin)
[0060] The binder resin used in the conductive paste of the present embodiment includes cellulose, polyvinyl acetal, and a polymer compound in which a cellulose compound and a polyvinyl acetal compound are bonded via sulfur atoms, wherein the molar ratio of sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose compound is 0.3 to 1.7.
[0061] That is, the binder resin used in the conductive paste of the present embodiment includes a polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound. Moreover, the number average molecular weight (Mn) of the polymer compound is preferably 20,000 to 200,000 based on the standard polystyrene conversion value based on gel permeation chromatography (GPC). Moreover, the content of the polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound is preferably 1 part by mass or more and 10 parts by mass or less, and more preferably 1 part by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the conductive powder.
[0062] The polymer compound of the present embodiment has a portion formed of a cellulose compound and a portion formed of a polyvinyl acetal compound, so the dry film obtained from the conductive paste of the present embodiment can have surface smoothness due to the cellulose compound and adhesion to the green sheet due to the polyvinyl acetal compound. Furthermore, the polymer compound can also eliminate poor dispersion of the conductive paste by having incompatible structures of the cellulose compound and the polyvinyl acetal compound in the same molecule.
[0063] Here, even if the molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.5 to 2, the surface roughness of the dry film is excellent compared to the conventional conductive paste using cellulose and polyvinyl acetal resin as binder resins, but if the molar ratio is 0.3 to 1.7, the surface roughness and dry film density of the dry film of the conductive paste are more excellent. The molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based polymer compound is 0.3 to 1.7, and more preferably the molar ratio is 0.5 to 1.5.
[0064] The polymer compound in which the cellulose-based compound and the polyvinyl acetal-based compound are bonded and which can be used in the present embodiment will be described in more detail.
[0065] Both cellulose and polyvinyl acetal have hydroxyl groups in the molecule. Cellulose compounds and polyvinyl acetal compounds are prepared. The cellulose compounds are formed by introducing functional groups that can react with other compounds to form bonds in the hydroxyl groups of cellulose, and chemically modifying them with reactive functional groups. On the other hand, the polyvinyl acetal compounds are formed by introducing functional groups that can react with other compounds to form bonds and are different from the functional groups introduced into the cellulose compounds in the hydroxyl groups of polyvinyl acetal polymer compounds, and chemically modifying them with reactive functional groups. That is, the reactive functional groups introduced into the cellulose compounds are different from the reactive functional groups introduced into the polyvinyl acetal compounds. In addition, the functional groups introduced into the cellulose compounds react with the functional groups introduced into the polyvinyl acetal compounds, but it is difficult to react between the same functional groups. Here, it is difficult to react between the same functional groups to avoid the situation where the cellulose compounds and the polyvinyl acetal compounds are bonded to each other.
[0066] Moreover, if the functional group introduced into the cellulose compound is bonded with the functional group introduced into the polyvinyl acetal compound, a polymer compound formed by bonding the cellulose compound and the polyvinyl acetal compound can be obtained. Specifically, if a thiol group is introduced into cellulose to make a cellulose compound, and a vinyl group is introduced into a polyvinyl acetal resin to make a polyvinyl acetal compound, then the thiol group and the vinyl group are in the presence of a nucleophilic reagent and under the condition of generating free radicals, the double bond of the vinyl group is bonded to the sulfur atom of the thiol group. As a polymer compound of the binder resin used in the conductive paste of the present embodiment, a polymer compound formed by bonding the thiol group and the vinyl group can be obtained by utilizing the bonding reaction of the thiol group and the vinyl group. Of course, vinyl groups can also be introduced into the hydroxyl group of cellulose to make a cellulose compound, and thiol groups can be introduced into the hydroxyl group of the polyvinyl acetal resin to make a polyvinyl acetal compound.
[0067] That is, the cellulose-based compound may be a cellulose derivative having a thiol group or a vinyl group, and the polyvinyl acetal-based compound may be a polyvinyl acetal resin having a thiol group or a vinyl group. Furthermore, when the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group that reacts with the thiol group, and when the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group that reacts with the vinyl group.
[0068] The cellulose-based polymer compound used as the binder resin of the conductive paste of this embodiment is preferably a polymer compound in which the hydroxyl groups of cellulose, which is a natural polymer, are bonded to a compound and chemically modified. The chemical modification here is different from the chemical modification of introducing a reactive functional group as described above.
[0069] The bonding of the compound with the hydroxyl group of cellulose can be exemplified by alkyl etherification, esterification, etc. Examples of cellulose having a hydroxyl group include methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxybutyl methyl cellulose, cellulose acetate (acetyl cellulose, diacetyl cellulose, triacetyl cellulose, etc.), cellulose acetate propionate, cellulose acetate butyrate, nitrocellulose, etc. Cellulose may be used alone or in combination of two or more.
[0070] Since the conductive paste of the embodiment contains an organic solvent, it is preferred that cellulose also dissolves in the organic solvent. From the viewpoint of solubility in the organic solvent and smoothness of a dried film of the conductive paste, ethyl cellulose is more preferably used as the cellulose.
[0071] The molecular weight of cellulose affects the viscosity of the conductive paste of the present embodiment. The number average molecular weight (Mn) of cellulose is preferably 10,000 to 100,000, more preferably 10,000 to 80,000, in terms of standard polystyrene conversion value based on GPC.
[0072] When the number average molecular weight of cellulose is less than 10,000, the viscosity of the conductive paste becomes low, and when the number average molecular weight of cellulose exceeds 100,000, the viscosity of the conductive paste may become too high.
[0073] Not all hydroxyl groups of cellulose are chemically modified. The glucose ring that makes up cellulose has three hydroxyl groups, but if we average the number of hydroxyl groups per glucose ring of cellulose, 0.1 to 1 hydroxyl group remains unchanged and is not chemically modified. In this way, reactive functional groups are introduced into the hydroxyl groups that have not been chemically modified.
[0074] On the other hand, polyvinyl acetal is generally a polymer composed of monomer units of vinyl acetal / vinyl alcohol / vinyl acetate, and can be obtained by saponifying polyvinyl acetate to form polyvinyl alcohol, and then acetalizing the polyvinyl alcohol. Specifically, acetal (polyvinyl butyral) obtained by butyralizing polyvinyl alcohol, acetal (polyvinyl formal) obtained by formalizing polyvinyl alcohol, etc. can be cited.
[0075] The polyvinyl acetal may be a commercially available product, and various polyvinyl acetals having different degrees of butyralization, formalization, acetyl group content, hydroxyl group content, molecular weight, etc. are sold by Sekisui Chemical Co., Ltd., Kuraray Co., Ltd., etc. The polyvinyl acetal may be used alone or in combination of two or more.
[0076] The polyvinyl acetal is preferably soluble in an organic solvent. From the viewpoint of high solubility in an organic solvent, the polyvinyl acetal is more preferably polyvinyl butyral.
[0077] Polyvinyl acetal affects film strength and solution viscosity according to its molecular weight. Therefore, the number average molecular weight of polyvinyl acetal is preferably in the range of 5,000 to 150,000, more preferably in the range of 10,000 to 100,000, in terms of standard polystyrene conversion value based on GPC.
[0078] If the number average molecular weight of polyvinyl acetal is less than 5,000, the solution viscosity becomes extremely low, and viscosity adjustment of the inorganic particle-containing composition (slurry or slurry) becomes difficult. In addition, there is a risk that the strength and adhesion of the film formed by applying and drying the inorganic particle-containing composition will be reduced.
[0079] Polyvinyl acetal has at least one hydroxyl group in one molecule. Generally, polyvinyl acetal has 20 to 40 mol% of hydroxyl groups as vinyl alcohol units constituting the polymer. A reactive functional group is introduced into the hydroxyl group for chemical modification.
[0080] As the compound that reacts with the hydroxyl group of cellulose to chemically modify it, a compound having a thiol group or a vinyl group at one end and a carboxyl group at the other end can be used. The carboxyl group of the compound forms an ester bond with the hydroxyl group of the cellulose-based polymer compound by dehydration condensation.
[0081] A method for synthesizing the polymer compound used in this embodiment will be described.
[0082] In order to obtain a cellulose-based compound or a polyvinyl acetal-based compound, a compound having the following functional groups, i.e., a functional group reactive with a hydroxyl group and a functional group reactive with other compounds, can be esterified or etherified with the hydroxyl group of cellulose or the hydroxyl group of polyvinyl acetal. Examples of the functional group reactive with a hydroxyl group include a carboxyl group and a hydroxyl group.
[0083] The esterification reaction can be carried out using a condensing agent, for example. Examples of the condensing agent include carbodiimide, diphenylphosphoryl azide, 1-hydroxybenzotriazole, and the like. The condensing agent can be used alone or in combination of two or more. Among them, carbodiimide is preferred because of its versatility and excellent reactivity, and can react under low temperature conditions without being affected by moisture in the reaction environment.
[0084] Examples of carbodiimide include dicyclohexylcarbodiimide, diisopropylcarbodiimide, N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide, and N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide methyl iodide. Among them, dicyclohexylcarbodiimide and diisopropylcarbodiimide are preferred from the viewpoint of availability. In addition, when using carbodiimide, it is also preferred to use dimethylaminopyridine or triethylamine as a base in a range of 0.01 mol% to 10 mol% relative to the carbodiimide as a reaction accelerator.
[0085] The etherification reaction can be efficiently carried out by using an alkali metal hydroxide such as KOH and NaOH; or an alkali metal hydride such as NaH and KH as a reaction catalyst.
[0086] In order to obtain a cellulose-based compound, it is also preferred to dissolve cellulose in an aprotic solvent such as ethyl acetate, mix a compound having a carboxyl group that is ester-bonded with a hydroxyl group and a vinyl or thiol group as a functional group that reacts with other compounds, and use a condensing agent and dimethylaminopyridine as a base such as a nucleophilic reagent for promoting the esterification reaction in an amount within a range of 0.01 mol % to 10 mol %.
[0087] The molar ratio of sulfur atoms in the polymer compound used in the present embodiment to the total of cellulose and cellulose-based compounds is 0.3 to 1.7. Therefore, 0.3 to 1.7 mol of a compound having a functional group reactive with other compounds needs to be added to 1 mol of cellulose.
[0088] The reaction temperature for synthesizing the cellulose-based compound is preferably in the range of room temperature to 50°C.
[0089] In the system where the synthesis reaction of the cellulose compound is completed, unreacted cellulose without the introduction of a hydroxyl group and a functional group reactive with other compounds, a cellulose compound introduced with one reactive functional group, and a cellulose compound introduced with multiple reactive functional groups are mixed. Chemical modification is a matter of probability, but the cellulose compound in which one hydroxyl group of cellulose is chemically modified is the most common. Then, after the synthesis of the cellulose compound is completed, the solvent can be removed by distillation.
[0090] In order to synthesize polyvinyl acetal compounds, it is also preferred to dissolve polyvinyl acetal in an aprotic solvent such as ethyl acetate, mix a compound having a carboxyl group that is ester-bonded with a hydroxyl group and a vinyl group or a thiol group as a functional group that reacts with other compounds, and use a condensing agent and dimethylaminopyridine as a base such as a nucleophilic reagent for promoting the esterification reaction in an amount within a range of 0.01 mol% to 10 mol%.
[0091] The reaction temperature for chemical modification of the hydroxyl group of polyvinyl acetal is preferably in the range of room temperature to 50° C. Then, after the synthesis of the polyvinyl acetal-based compound is completed, the solvent may be distilled off.
[0092] The polymer compound used in the present embodiment is prepared by dissolving a cellulose compound and a polyvinyl acetal compound in a solvent, adding a free radical generator and heating, thereby reacting a vinyl group possessed by one of the cellulose compound and the polyvinyl acetal compound with a thiol group possessed by the other, thereby bonding the cellulose compound and the polyvinyl acetal compound.
[0093] Alternatively, the cellulose compound and the polyvinyl acetal compound may be dissolved in a solvent, and a nucleophilic reagent represented by a base such as amine may be added and heated.
[0094] The temperature of the reaction for bonding the cellulose compound and the polyvinyl acetal compound can be appropriately selected, but is preferably 60° C. or higher.
[0095] The solvent may be an acetate solvent such as dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate, isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, or a terpene solvent such as terpineol and dihydroterpineol. If the solvent used in the conductive paste is used as the solvent, a carrier in which the obtained polymer compound is dissolved in the solvent may be prepared.
[0096] In this embodiment, in addition to the polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound, a cellulose resin such as methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, an acrylic resin, a butyral resin such as a polyvinyl acetal resin, etc. can be added. The molecular weight of the resin that can be added is about 20,000 to 200,000 in terms of GCP.
[0097] The content of the binder resin is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass, relative to the total amount of the conductive paste. When the content of the binder resin is within the above range, the conductivity and dispersibility are excellent.
[0098] For example, the cellulose derivative may be ethyl cellulose having a thiol group or a vinyl group, and the polyvinyl acetal resin may be polyvinyl butyral having a thiol group or a vinyl group.
[0099] Specifically, the cellulose-based compound may be a first esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose, and the polyvinyl acetal-based compound may be a second esterification product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of polyvinyl acetal. Furthermore, when the first esterification product has a thiol group, the second esterification product may have a vinyl group, and when the first esterification product has a vinyl group, the second esterification product may have a thiol group, and the polymer compound may be a thiol-ene reaction product of the first esterification product and the second esterification product.
[0100] More specifically, the first esterification product may be a product formed by dehydration condensation of the carboxyl group of 3-allyloxypropionic acid and the hydroxyl group of ethyl cellulose, and the second esterification product may be a product formed by dehydration condensation of the carboxyl group of 3-mercaptopropionic acid and the hydroxyl group of polyvinyl butyral.
[0101] (Organic Solvent)
[0102] The organic solvent is not particularly limited, and a known organic solvent that can dissolve the above-mentioned binder resin can be used. As the organic solvent, for example, acetate solvents such as dihydroterpineol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate and isobornyl isobutyrate, ethylene glycol monomethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, and dipropylene glycol methyl ether acetate, terpene solvents such as terpineol and dihydroterpineol, hydrocarbon solvents such as tridecane, nonane, and cyclohexane, and petroleum hydrocarbon solvents such as mineral spirits can be cited. In addition, the organic solvent can be used alone or in combination.
[0103] The content of the organic solvent is preferably 40 parts by mass or more and 100 parts by mass or less, and more preferably 65 parts by mass or more and 95 parts by mass or less, based on 100 parts by mass of the conductive powder. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0104] The content of the organic solvent is preferably 20% by mass or more and 60% by mass or less, and more preferably 35% by mass or more and 55% by mass or less, relative to the total amount of the conductive paste. When the content of the organic solvent is within the above range, the conductivity and dispersibility are excellent.
[0105] (Dispersant)
[0106] The conductive paste of this embodiment may include a dispersant. The function of the dispersant is to adsorb on the surface of the inorganic powder (conductive powder and ceramic powder) to inhibit the aggregation of the inorganic powders, or to improve the wettability with the organic carrier to disperse it in the conductive paste. The dispersant (surfactant) may include an acid dispersant containing a higher fatty acid, a polymer surfactant, etc., a cationic dispersant other than the acid dispersant, a nonionic dispersant, an amphoteric surfactant, and a polymer dispersant.
[0107] The dispersant may be selected alone or in combination. The content of the conductive paste may be appropriately selected in consideration of the viscosity, tack, long-term storage stability, etc. of the conductive paste, and may be contained within a range that does not impair the effects of the present invention.
[0108] In addition, the mass average molecular weight of the dispersant is preferably 200 to 100,000. More preferably, it is 300 to 30,000. If the mass average molecular weight is less than 200, sometimes the particles do not obtain sufficient electrostatic repulsion, and the dispersibility and storage stability of the particles are reduced. Usually, the dispersant is adsorbed on the surface of the particles to form an adsorption layer of the dispersant, which imparts electrostatic repulsion and steric repulsion to the particles, thereby obtaining a slurry with excellent dispersibility. However, it is believed that over time, due to the collision of the particles, the particles overcome the repulsive force of the adsorption layer and agglomerate with each other, so the mass average molecular weight is preferably above 200. In addition, if the mass average molecular weight is greater than 100,000, sometimes the compatibility with the organic carrier and the organic solvent is reduced, or the particles are agglomerated with each other, or the dispersibility and storage stability are reduced. In addition, there is also the problem of increased slurry viscosity.
[0109] The amount of the dispersant added is preferably 0.01 to 5.00 parts by mass, more preferably 0.20 to 2.00 parts by mass, relative to 100 parts by mass of the conductive metal powder content. When the dispersant is less than 0.01 parts by mass, it tends to be difficult to obtain sufficient dispersibility. On the other hand, when it exceeds 5.00 parts by mass, the drying property deteriorates, and the problem of reduced dry film density occurs.
[0110] (Method for producing conductive paste)
[0111] The manufacturing method of the conductive paste of the present embodiment is not particularly limited, and a conventionally known method can be used. The conductive paste can be manufactured, for example, by preparing the above-mentioned components and stirring and kneading them using a three-roll mill, a ball mill, a mixer, etc. At this time, if a dispersant is pre-coated on the surface of the conductive powder, the conductive powder will not agglomerate but will be fully dispersed, and the dispersant will be spread all over its surface, making it easy to obtain a uniform conductive paste. In addition, the binder resin can also be dissolved in an organic solvent for the carrier to prepare an organic carrier, and conductive powder, ceramic powder, organic carrier and dispersant are added to the organic solvent for the slurry, and stirred and kneaded with a mixer to prepare a conductive paste.
[0112] In addition, as the organic solvent for the carrier, in order to improve the affinity of the organic carrier, it is preferred to use the same organic solvent as the organic solvent for adjusting the viscosity of the conductive paste. The content of the organic solvent for the carrier is, for example, 5 parts by mass or more and 80 parts by mass or less relative to 100 parts by mass of the conductive powder. In addition, the content of the organic solvent for the carrier is preferably 10% by mass or more and 40% by mass or less relative to the total amount of the conductive paste.
[0113] The surface smoothness of the dry film formed by printing the conductive paste can be evaluated by surface roughness. In addition, the surface roughness of the conductive paste can be measured, for example, by the method described in the examples (using VK-X120 manufactured by KEYENCE, based on the standard of ISO 25178, to measure the arithmetic mean height Sa). When the arithmetic mean height Sa is used for evaluation, the surface smoothness of the dry film is preferably less than 0.10 μm.
[0114] [Electronic components, multilayer ceramic capacitors]
[0115] The conductive paste of the present invention can be suitably used in electronic components such as multilayer ceramic capacitors. Multilayer ceramic capacitors have dielectric layers formed using green sheets and internal electrode layers formed using conductive paste.
[0116] The dielectric ceramic powder contained in the green sheet of the multilayer ceramic capacitor and the ceramic powder contained in the conductive paste are preferably powders of the same composition, for example, barium titanate can be used. The multilayer ceramic capacitor manufactured using the conductive paste of this embodiment can suppress sheet erosion and poor peeling of the green sheet even when the thickness of the green sheet is, for example, 3 μm or less.
[0117] Hereinafter, embodiments of the electronic component and the like of the present invention will be described with reference to the accompanying drawings. In the accompanying drawings, the drawings may be schematically illustrated or scaled appropriately. Figure 1The position and direction of the member are described using an XYZ orthogonal coordinate system shown in FIG. In the XYZ orthogonal coordinate system, the X direction and the Y direction are horizontal directions, and the Z direction is a vertical direction (up and down direction).
[0118] Figure 1 A in and Figure 1 B in FIG. 1 is a perspective view and a side cross-sectional view showing a multilayer ceramic capacitor 1 as an example of the electronic component according to the embodiment. The multilayer ceramic capacitor 1 includes a ceramic multilayer body 10 in which dielectric layers 12 and internal electrode layers 11 are alternately stacked, and external electrodes 20 .
[0119] The following is a description of a method for manufacturing a multilayer ceramic capacitor 1 using the above-mentioned conductive paste. First, a conductive paste is printed on a dielectric layer composed of a green sheet and dried to form a dry film. After a plurality of dielectric layers having the dry film on the upper surface are stacked and pressed to obtain a laminate, the laminate is fired and integrated to produce a ceramic laminate 10 in which internal electrode layers 11 and dielectric layers 12 are alternately stacked. Thereafter, a pair of external electrodes 20 are formed at both ends of the ceramic laminate 10 to manufacture the multilayer ceramic capacitor 1. The following is a more detailed description.
[0120] First, an unfired ceramic sheet using a dielectric material, i.e., a green sheet, is prepared. Examples of the ceramic green sheet include: a dielectric layer slurry obtained by adding an organic binder such as polyvinyl butyral and a solvent such as terpineol to a raw material powder of a predetermined ceramic such as barium titanate, and applying the slurry in a sheet form on a supporting film such as a PET film, and drying the slurry to remove the solvent. In addition, the thickness of the dielectric layer formed by the green sheet is not particularly limited, but from the perspective of the miniaturization requirement of the multilayer ceramic capacitor, it is preferably 0.05 μm or more and 3 μm or less.
[0121] Next, on one side of the green sheet, a plurality of sheets are prepared by printing (coating) the above-mentioned conductive paste by a known method such as screen printing and drying to form a dry film. In addition, from the viewpoint of the requirement for thinning the internal electrode layer 11, the thickness of the conductive paste (dry film) after printing is preferably set to a thickness of 1 μm or less after drying.
[0122] Next, the green sheet is peeled off from the support film, and the dielectric layers composed of the green sheets and the dry films formed on one side thereof are alternately stacked, and then heated and pressurized to obtain a laminate. In addition, a protective green sheet not coated with conductive paste may be further arranged on both sides of the laminate.
[0123] Next, after the laminate is cut into a predetermined size to form a raw chip, the raw chip is subjected to a debinding treatment and fired in a reducing atmosphere, thereby manufacturing a ceramic laminate 10. In addition, the atmosphere in the debinding treatment is preferably set to air or N2 gas atmosphere. The temperature during the debinding treatment is, for example, above 200°C and below 400°C. In addition, it is preferred that the holding time of the above temperature during the debinding treatment is set to be above 0.5 hours and below 24 hours. In addition, in order to suppress the oxidation of the metal used for the internal electrode layer, the firing is carried out in a reducing atmosphere. In addition, the temperature during the firing of the laminate is, for example, above 1000°C and below 1350°C, and the holding time of the temperature during the firing is, for example, above 0.5 hours and below 8 hours.
[0124] By firing the green chip, the organic binder in the green chip is completely removed, and the raw material powder of the ceramic is fired to form the ceramic dielectric layer 12. In addition, the organic vehicle in the dry film is removed, and the nickel powder or the alloy powder mainly composed of nickel is sintered or melted and integrated to form the internal electrode layer 11, thereby forming a laminated ceramic fired body in which a plurality of dielectric layers 12 and internal electrode layers 11 are alternately stacked. In addition, from the viewpoint of introducing oxygen into the interior of the dielectric layer to improve reliability and suppressing reoxidation of the internal electrode, the laminated ceramic fired body after firing may be subjected to annealing treatment.
[0125] Then, a pair of external electrodes 20 are provided on the manufactured multilayer ceramic fired body, thereby manufacturing the multilayer ceramic capacitor 1. For example, the external electrode 20 includes an external electrode layer 21 and a plating layer 22. The external electrode layer 21 is electrically connected to the internal electrode layer 11. In addition, as a material of the external electrode 20, for example, copper, nickel, or an alloy thereof can be preferably used. In addition, the electronic component is not limited to the multilayer ceramic capacitor, and may also be an electronic component other than the multilayer ceramic capacitor such as a varistor.
[0126] Example
[0127] Hereinafter, the present invention will be described in detail based on Examples and Comparative Examples, but the present invention is not limited to these Examples at all.
[0128] [Materials used]
[0129] (Conductive powder)
[0130] As the conductive powder, Ni powder (number average particle size measured by SEM: 0.2 μm) was used.
[0131] (Ceramic powder)
[0132] As the ceramic powder, barium titanate (BaTiO 3 ; number average particle size based on SEM measurement: 0.05 μm) was used.
[0133] (Binder resin)
[0134] The binder resin was synthesized as follows.
[0135] (Synthesis of Cellulose Compound (1a) Having Vinyl Group)
[0136] Ethyl cellulose ("ETHOCEL STD-100" manufactured by Dow Chemical, number average molecular weight Mn (standard polystyrene conversion value based on GPC): 63420, average number of unetherified hydroxyl groups per glucose ring: 0.48) was prepared and dried.
[0137] 100 parts by mass of the dried ethyl cellulose was dissolved in 900 parts by mass of ethyl acetate to obtain a solution. 0.17 parts by mass of 3-allyloxypropionic acid, 0.20 parts by mass of diisopropylcarbodiimide as a condensing agent, and 0.004 parts by mass of dimethylaminopyridine as a reaction accelerator were added to the obtained solution, and the mixture was stirred at a temperature of 40° C. for 5 hours to react. Thereafter, the ethyl acetate was removed to obtain a cellulose-based compound (1a) in which a vinyl group was introduced into the ethyl cellulose as a solid.
[0138] A portion of the obtained solid was analyzed by FT-IR and 1H-NMR, and as a result, it was confirmed that an ester bond was generated and that a vinyl group in an amount equivalent to the molar amount of 3-allyloxypropionic acid charged was introduced into ethyl cellulose.
[0139] In the cellulose compound (1a), in addition to the compound in which a vinyl group is introduced into ethyl cellulose, unreacted ethyl cellulose is mixed, but in the examples, the mixture is referred to as the cellulose compound (1a). The same is true for the cellulose compound (2a) and the cellulose compound (3a) described later.
[0140] (Synthesis of polyvinyl butyral compound (1b) having a thiol group)
[0141] Polyvinyl butyral ("BM-SZ" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn (based on standard polystyrene conversion value of GPC): 55000, hydroxyl content: about 22 mol%) was prepared and dried. 100 parts by mass of the dried polyvinyl butyral was dissolved in 900 parts by mass of ethyl acetate. 0.20 parts by mass of 3-mercaptopropionic acid, 0.24 parts by mass of diisopropylcarbodiimide as a condensing agent, and 0.005 parts by mass of dimethylaminopyridine as a reaction accelerator were added to the obtained solution in an amount corresponding to an average of one thiol group introduced per molecule of polyvinyl butyral, and the mixture was stirred at a temperature of 40°C for 5 hours to react. Thereafter, by removing ethyl acetate, a polyvinyl butyral-based compound (1b) in which a thiol group was introduced into the polyvinyl butyral was obtained as a solid.
[0142] A portion of the obtained solid was analyzed by FT-IR and 1H-NMR, and as a result, it was confirmed that an ester bond was generated and that thiol groups in an amount equivalent to the molar amount of 3-mercaptopropionic acid charged were introduced into polyvinyl butyral.
[0143] In addition, in the polyvinyl butyral compound (1b), unreacted polyvinyl butyral is mixed with the compound having a thiol group introduced into the polyvinyl butyral, but in the examples, the mixture is referred to as the polyvinyl butyral compound (1b). The same applies to the polyvinyl butyral compound (2b) and the polyvinyl butyral compound (3b) described later.
[0144] (Synthesis of Cellulose Compounds (2a, 3a) Having Vinyl Groups)
[0145] Cellulose compounds (2a) and (3a) were synthesized in the same manner as in the cellulose compound (1a), except that 3-allyloxypropionic acid was added in an amount corresponding to an average of 0.5 or 2 molecules per molecule of ethyl cellulose.
[0146] (Synthesis of polyvinyl butyral compounds (2b, 3b) having a thiol group)
[0147] Polyvinyl butyral compounds (2b) and (3b) were synthesized in the same manner as the polyvinyl butyral compound (1b), except that 3-mercaptopropionic acid was added in an amount corresponding to an average of 0.5 or 2 molecules per polyvinyl butyral molecule.
[0148] (Synthesis of Polymer Compound 1)
[0149] 5 parts by mass of a cellulose compound (1a) and 4.35 parts by mass of a polyvinyl butyral compound (1b) were dissolved in 60 parts by mass of dihydroterpineol as a solvent, and the solution was transferred to a glass flask reaction container. After nitrogen substitution, 0.1 parts by mass of azobisisobutyronitrile as a free radical generator was added to the solution, and the mixture was reacted at 80°C for 3 hours with stirring to obtain an organic vehicle 1 containing a polymer compound 1. Here, the cellulose compound (1a) and the polyvinyl butyral compound (1b) were the same in molar number. As described above, an average of one thiol group was introduced per polyvinyl butyral molecule, and therefore the molar ratio of sulfur atoms contained in the polymer compound 1 to the total of cellulose and the cellulose compound was 1. The organic vehicle 1 contained 13.5% by mass of the polymer compound 1. In addition, in the polymer compound 1, a polymer compound formed by bonding the cellulose compound (1a) and the polyvinyl butyral compound (1b) was mixed with unreacted ethyl cellulose and unreacted polyvinyl butyral.
[0150] The generated polymer compound 1 was analyzed by FT-IR and 1H-NMR, and as a result, -S- bonds were confirmed, and the target structure was obtained. Furthermore, the number average molecular weight (Mn: standard polystyrene conversion value based on GPC) of the polymer compound 1 was measured.
[0151] Polymer compound 2 synthesized from cellulose compound (2a) and polyvinyl butyral compound (2b), and polymer compound 3 synthesized from cellulose compound (3a) and polyvinyl butyral compound (3b) were synthesized in the same manner as polymer compound 1, and the presence of -S- bonds was confirmed and the number average molecular weight was measured to obtain organic carrier 2 and organic carrier 3. In addition, the content of polymer compound 2 in organic carrier 2 was 13.5% by mass, and the content of polymer compound 3 in organic carrier 3 was 13.5% by mass. In addition, in polymer compound 2, similar to polymer compound 1, a polymer compound formed by bonding cellulose compound (2a) and polyvinyl butyral compound (2b) was mixed with unreacted ethyl cellulose and unreacted polyvinyl butyral. The same is true for polymer compound 3. Here, the cellulose compound (2a) and the polyvinyl butyral compound (2b) have the same molar number, and as described above, an average of 0.5 thiol groups are introduced per molecule of polyvinyl butyral, so the molar ratio of sulfur atoms contained in the polymer compound 2 to the total of cellulose and the cellulose compound is 0.5. In addition, the cellulose compound (3a) and the polyvinyl butyral compound (3b) have the same molar number, and as described above, an average of 2 thiol groups are introduced per molecule of polyvinyl butyral, so the molar ratio of sulfur atoms contained in the polymer compound 3 to the total of cellulose and the cellulose compound is 2.
[0152] Table 1 shows the characteristics of the cellulose compounds (1a) to (1c) and polyvinyl acetal compounds (1b) to (3b) used in polymer compounds 1 to 3.
[0153] In addition, polymer compound 1 contains unreacted ethyl cellulose and polyvinyl butyral in addition to the reaction product of cellulose compound (1a) and polyvinyl butyral compound (1b), but in the examples, the mixture is referred to as polymer compound 1. The same applies to polymer compounds 2 and 3.
[0154]
[0155] [Example 1]
[0156] 47% by mass of Ni powder, 4.7% by mass of ceramic powder, 26.67% by mass of organic vehicle 1, 0.4% by mass of anionic dispersant of amide compound of amino acid and fatty acid (hereinafter referred to as dispersant A), and 21.23% by mass of organic solvent (dihydroterpineol) were mixed so as to make a total of 100% by mass, and these materials were prepared to prepare a conductive paste. The prepared conductive paste was printed and dried as follows, and the surface roughness of the obtained dry film and its close adhesion to the raw sheet were evaluated. The evaluation results are shown in Tables 2 and Figure 2 .
[0157] [Evaluation method]
[0158] (Dispersibility: Surface roughness of the dry film and adhesion to the green sheet)
[0159] <Surface Roughness>
[0160] The conductive paste produced by screen printing is placed on a 2.54 cm (1 inch) square heat-resistant tempered glass and dried at 120 ° C for 1 hour in the atmosphere to produce a 20 mm square dry film with a film thickness of 1 to 3 μm. When the dispersibility of the conductive paste is good, the surface of the dry film is formed into a smooth film. In the case of poor dispersibility, agglomeration occurs in the conductive paste, the surface of the dry film is rough, and the smoothness of the surface is reduced. Therefore, a laser microscope (VK-X120 manufactured by KEYENCE) is used to measure the surface roughness Sa (arithmetic mean height) of the produced dry film based on the standard of ISO 25178. The smaller the value of the surface roughness Sa (arithmetic mean height), the smoother the surface of the dry film.
[0161] Furthermore, the obtained dried film was observed by SEM.
[0162] <Adhesion between dry film and green sheet>
[0163] The conductive paste was prepared and the printer was adjusted in such a way that the film thickness after printing was 3.6 μm, and a 2 cm square pattern was printed on a 2.54 cm (1 inch) square BaTiO3 dielectric green sheet. After printing, it was dried at 120°C for 20 minutes to form a dry film of the conductive paste on the surface of the green sheet. The BaTiO3 dielectric green sheet was covered on the dry film of the conductive paste, and the dry film of the conductive paste and the BaTiO3 dielectric green sheet were hot pressed with an isostatic press at 80°C and 98 MPa to produce a laminate. The adhesion of the dry film of the conductive paste and the dry film to the BaTiO3 dielectric green sheet of the obtained laminate was evaluated by measuring the force of peeling off the dry film of the conductive paste and the BaTiO3 dielectric green sheet. The adhesion was measured by a thin film adhesion strength measuring machine (Romulus manufactured by Photo Technica). Specifically, the adhesion evaluation process in the film adhesion strength tester is described. An aluminum anti-skid spike coated with epoxy adhesive is vertically bonded to the center of the laminate, and a sample for adhesion evaluation to which the anti-skid spike is vertically bonded is prepared. The anti-skid spike of the sample is pulled so as to be peeled off from the surface of the laminate, thereby evaluating the adhesion between the dry film of the conductive paste and the BaTiO3 dielectric green sheet. In addition, the adhesion evaluation results are shown as relative evaluation results with the adhesion strength of Comparative Example 2 described later being 100.
[0164] [Example 2]
[0165] The results are shown in Table 2.
[0166] [Example 3]
[0167] A conductive paste was prepared and evaluated in the same manner as in Example 2 except that a high molecular weight polycarboxylic acid anionic dispersant (hereinafter referred to as dispersant B) was used. The results are shown in Tables 2 and 3. Figure 2 .
[0168] [Comparative Example 1]
[0169] A conductive paste was prepared and evaluated in the same manner as in Example 1 except that the organic vehicle 3 containing the polymer compound 3 was used.
[0170] [Comparative Example 2]
[0171] 5 parts by mass of ethyl cellulose ("ETHOCEL STD-100" manufactured by Dow Chemical, number average molecular weight Mn (standard polystyrene conversion value based on GPC): 63420, average number of unetherified hydroxyl groups per glucose ring: 0.48) was dissolved in 30 parts by mass of terpineol to prepare an organic carrier 4a.
[0172] 4.35 parts by mass of polyvinyl butyral resin ("BM-SZ" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn (standard polystyrene conversion value based on GPC): 55000, hydroxyl content: about 22 mol%) was dissolved in 30 parts by mass of terpineol to prepare carrier 4b. Then, equal amounts of organic carrier 4a and organic carrier 4b were mixed to prepare organic carrier 4.
[0173] 47% by mass of Ni powder, 4.7% by mass of ceramic powder, 26.67% by mass of organic vehicle 4, 0.4% by mass of dispersant A, and 21.23% by mass of the remaining organic solvent (dihydroterpineol) were mixed so that the total amount was 100% by mass, and these materials were mixed to prepare a conductive paste. The obtained paste was evaluated in the same manner as in Example 1. The results are shown in Tables 3 and 4. Figure 2 Comparative Example 2 is an example of a conventionally known conductive paste using ethyl cellulose and polyvinyl butyral resin in combination.
[0174]
[0175] Table 3
[0176]
[0177] [Evaluation results]
[0178] As shown in Table 2, the surface roughness Sa (arithmetic mean height) of the conductive pastes of Examples 1, 2, and 3 was 0.10 μm or less. Furthermore, as shown in the SEM photographs in Table 2, it is found that the surface roughness is small and is superior to Comparative Example 2 of the conventionally known structure.
[0179] In contrast, as shown in Table 3, the surface roughness Sa of the conductive pastes of Comparative Examples 1 and 2 is 0.11 μm or more. In addition, as shown in the SEM photograph, Comparative Example 1 has fewer irregularities than Comparative Example 2 of the prior art. However, considering the miniaturization and thinning of multilayer ceramic electronic components in the future, it can be confirmed that the smoothness of the dried film of Comparative Example 1 is inferior to that of Examples 1 and 2.
[0180] Further, according to Figure 2 It is found that Example 1 and Example 3, which are excellent in surface roughness Sa, are also excellent in adhesion between the dried film of the conductive paste and the BaTiO 3 dielectric green sheet compared to Comparative Example 2.
[0181] Industrial Applicability
[0182] The conductive paste according to the present embodiment using micronized conductive powder and ceramic powder can provide a conductive paste having a smooth dry film and excellent adhesion. Therefore, it can be particularly suitable for use as a raw material for internal electrodes of multilayer ceramic capacitors, which are chip components (electronic components) of electronic devices such as mobile phones and digital devices.
[0183] Description of Reference Numerals
[0184] 1: Multilayer ceramic capacitor;
[0185] 10: Ceramic laminate;
[0186] 11: internal electrode layer;
[0187] 12: dielectric layer;
[0188] 20: external electrode;
[0189] 21: external electrode layer;
[0190] 22: Electroplating layer.
Claims
1. A conductive paste, wherein: The conductive paste comprises conductive powder, ceramic powder, dispersant, binder resin and organic solvent. The binder resin includes cellulose, polyvinyl acetal, and a polymer compound formed by bonding a cellulose compound and a polyvinyl acetal compound via a sulfur atom. The molar ratio of the sulfur atoms contained in the polymer compound to the total of the cellulose and the cellulose-based compound is 0.3 to 1.
7.
2. The conductive paste according to claim 1, wherein The cellulose-based compound is a cellulose derivative having a thiol group or a vinyl group, The polyvinyl acetal compound is a polyvinyl acetal resin having a thiol group or a vinyl group. When the cellulose derivative has a thiol group, the polyvinyl acetal resin has a vinyl group reactive with the thiol group. When the cellulose derivative has a vinyl group, the polyvinyl acetal resin has a thiol group reactive with the vinyl group.
3. The conductive paste according to claim 2, wherein: The cellulose derivative is ethyl cellulose having a thiol group or a vinyl group, The polyvinyl acetal resin is polyvinyl butyral having a thiol group or a vinyl group.
4. The conductive paste according to claim 1, wherein The cellulose-based compound is a first esterification reaction product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of cellulose, The polyvinyl acetal compound is a second esterification reaction product formed by dehydration condensation of a carboxyl group of a carboxylic acid having a thiol group or a vinyl group and a hydroxyl group of the polyvinyl acetal. When the first esterification reactant has a thiol group, the second esterification reactant has a vinyl group, When the first esterification reactant has a vinyl group, the second esterification reactant has a thiol group, The polymer compound is a thiol-ene reactant of the first esterification reactant and the second esterification reactant.
5. The conductive paste according to claim 4, wherein: The first esterification reactant is an esterification reactant formed by dehydration condensation of the carboxyl group of 3-allyloxypropionic acid and the hydroxyl group of ethyl cellulose, The second esterification reaction product is an esterification reaction product formed by dehydration condensation of the carboxyl group of 3-mercaptopropionic acid and the hydroxyl group of polyvinyl butyral.
6. The conductive paste according to claim 1 or 2, wherein: The conductive powder is nickel powder.
7. The conductive paste according to claim 1, wherein The number average particle size of the conductive powder is 0.05 μm or more and 1.0 μm or less.
8. The conductive paste according to claim 1, wherein The ceramic powder includes barium titanate.
9. The conductive paste according to claim 1, wherein: The ceramic powder has a number average particle size of 0.01 μm or more and 0.5 μm or less.
10. The conductive paste according to claim 1, wherein The content of the ceramic powder is 1 mass % or more and 20 mass % or less.
11. The conductive paste according to claim 1, wherein The conductive paste is used for internal electrodes of a multilayer ceramic component.
12. An electronic component, wherein: The electronic component is formed using the conductive paste according to claim 1.
13. A multilayer ceramic capacitor, wherein: The multilayer ceramic capacitor includes at least a laminated body in which a dielectric layer and an internal electrode layer are laminated. The internal electrode layer is formed using the conductive paste according to claim 1 .
Citation Information
Patent Citations
Printer
JP1977024722A
Method of electrolytically oxidizing metallic ions
JP1977099904A